Sensitive voltammetric determination of herbicide terbutryn using solid electrodes based on silver amalgam and boron-doped diamond - Šelešovská, Renáta; Janíková, Lenka; Pithardtová, Kristýna; Chýlková, Jaromíra; Tomášková, Markéta (My University, 2016)
The applicability of the mercury meniscus modified and polished silver solid amalgam electrode (m-, p-AgSAE) and boron-doped diamond electrode (BDDE) has been investigated for voltammetric analysis of herbicide terbutryn. Cyclic voltammetry and direct current voltammetry has been used for study of the voltammetric behavior of the analyzed substance depending on pH of supporting electrolyte and scan rate. Differential pulse voltammetry under the optimized experimental conditions has been applied for terbutryn determination using all tested electrodes with the limits of detection 2.9 x 10(-8) mol dm(-3) (m-AgSAE), 4.3 x 10(-9) mol dm(-3) (p-AgSAE), and 1.8 x 10(-7) mol dm(-3) (BDDE), respectively. Calculated values of relative standard deviations of repeated determinations (n = 5) in various concentration levels of terbutryn did not exceed 5 % for either of the tested electrodes. Finally, the developed methods have been successfully used in the analysis of the model samples. The obtained results were compared also with those achieved using hanging mercury drop electrode.
Citlivá voltametrická metoda stanovení herbicidu terbutrynu s využitím pevných elektrod založených na stříbrném amalgámu a borem dopovaném diamantu
Keywords: Electrochemistry; Voltammetry; Herbicide; Terbutryn; Silver solid amalgam electrode; Boron-doped diamond electrode; Elektrochemie; Voltametrie; Herbicidy; Terbutryn; Stříbrná pevná amalgámová elektroda; Borem dopovaná diamantová elektroda